The significant Role of the Ethical Tourism guide in developing the Tourism Patterns (The Peerian Journal, 2025)
Despite the consensus on the role of tourist guidance in promoting the destination and satisfying tourists, there is a lack of studies related to the role of tourist guidance in enhancing tourism patterns. In this context, the study aimed to identify the role of tourist guidance in developing ecotourism, halal tourism, and sustainable tourism. The study relied on the descriptive analytical approach and the quantitative approach and used the questionnaire as a tool to collect data from a random sample of tourists in the city of Karbala, the size of which was (70) individuals. The results of the study reached a high degree of answers of the study sample regarding the impact of the ethics of the tourist guidance profession on the development of ecotourism, halal tourism, and sustainable tourism, indicating that the commitment of tourist guides to the ethics of tourist guidance encourages the development of tourism patterns. The study recommended the development of a code of standards for the ethics of tourist guidance in Iraq and obligating tourist guides to comply with it.